Aplicación del marketing olfativo en las cadenas de supermercados de Guayaquil - Álava, L. (2009)
This paper work shows a new developed global marketing practice known as Sensory Brand or Aromarketing. On detail we review its possible inclusion to Guayaquil market by establishing a company (BML Aroma Creativo) that on a first basis will focus on its application in supermarkets. This, by implementing latest technology dispensers and offering as an added value, the creation of a personalized fragrance depending on the target market of the supermarket. This brand aroma will be established by an analytic study of the consumer, which will revise all the necessary characteristics for the creation of the fragrance. The business implementation feasibility will be measured through a financial analysis were three main aspects will be considered: Discount Rate (DR), Net Present Value (NPV) and the Internal Rate Return (IRR). Also, there will be a Sensitivity Analysis which will determine some variables and will evaluate how these affect the business yield (NPV and IRR), according to changes on these variables.